Síntesis y Caracterización de Nanopartícula s de NiS Mediante Procedimiento de Química Suave - Carrillo, Amanda (2020)
In this research, the synthesis and characterization of nickel sulphide (NiS) semiconductor nanoparticles (Nps) in solution is reported, the effect of glycine as complexing agent at different concentration was studied. The nanoparticles solutions were annealing 24 hours before characterization. From the characterization it was possible to define composition, optical properties as well as the distribution of nanoparticle size and morphology. The Nps exhibit spherical shape with sizes approximate of 80 nm as observed by SEM. The crystalline structure determined for the synthesized nanoparticles was orthorhombic. The nanoparticles in solution were also electrically characterized by electrical conductance measurements where the values obtained are between 431 and 765 uS, as the concentration of glycine increases the conductance decreases. The band gap determinate was 2.7 -2.9 eV, this reduced when the nanoparticles were prepared at low complexing agent. The functionality and applicability of the synthesis and processing reported here offers an alternative in the development of semiconductor materials to apply in semiconductor devices.